Yield and nitrogen uptake of peanuts as affected by lime, cobalt, and molybdenum - Rosolem, Ciro Antonio [UNESP]; Caires, E. F. (Taylor & Francis Inc, 1998)
Peanut response to lime has been associated to calcium (Ca) nutrition, but a higher nitrogen (N) uptake has been observed in limed plots probably due to an increase in molybdenum (Mo) availability. A two-year experiment was conducted to study the effects of Mo, cobalt (Co), and liming on peanut yields and N nutrition. Peanut seeds were treated with Mo and/or Co and grown in soil with base saturation about 13, 41, 57, and 71%. There was no effect of seed treatment with Co on peanut yields or N nutrition. Liming and Mo application increased N contents in the leaves. Nitrogen uptake was increased by Mo and liming in cv. Tatu and only by liming in cv. Tupa. Manganese (Mn) contents in the leaves were decreased by liming. The higher yields were observed when the Ca/Mn ratio in the leaves was above 25. In acid soils, low availability of Mo and Mn toxicity can impair N acquisition by peanut plants and decrease grain yields.